SIGNS OF PROBLEM LOANS AND THEIR QUALITY MANAGEMENT - Izbosarov Boburzhon Bakhriddinovich; Ulmasoy Akhmedova Khusan Kizi (Scholar Express Journal, 2025)
The article examines the signs of problem loans and defines them. In the modern banking sector, their role in the development of the economy as a whole is revealed; The mechanism and methods for managing problem loans in the modern banking sector are considered. The article describes their importance in economics, explains their functions and presents their features.
Keywords: “Problem”; loan portfolio; loan repayment